Identity in conflict: image and reality of Bangladeshis in Malaysia - Haque, Muhammed Shahriar (BRAC University, 2010)
Bangladeshis have often been associated with a nation that suffers from extreme poverty, embroiled in political turmoil, afflicted by floods, cyclones and by tragic accidents; these are the images that the mass media often portrays of Bangladesh internationally. Besides these associations, the media in Malaysia also focuses on the migrant workers and some of their isolated cases of criminal and antisocial activities. These activities portray a rather bleak and unwholesome picture of Bangladeshis in Malaysia and go towards creating an identity which is in conflict with the real identity of most Bangladesh nationals residing in this multicultural nation; hence, people in general develop a negative image of most Bangladeshis. This paper humbly attempts to show from a critical discourse analysis (CDA) perspective how the one sided media portrayal may contribute to the construction of an identity which not only contradicts but is also in conflict with the real identity of most Bangladeshi nationals—be they students, academics, professionals, businessmen or workers—residing in Malaysia. It is hoped that awareness of the issue from a CDA stance will help to dispel the stereotypical associations that more often than not may be triggered by portrayal of certain reports in the media.